Thermal ablation versus radiotherapy for inoperable stage III non-small cell lung cancer: a propensity score matching analysis - Yang, Wei-Yu; He, Yu; Peng, Muyun; Zhang, Zhe; Xie, Shouzhi; Wu, Zeyu; Hu, Qikang; Yu, Fenglei (International journal of hyperthermia, 2023)
To compare the survival benefits of thermal ablation (TA) and radiotherapy in inoperable patients with stage III non-small cell lung cancer (NSCLC). A retrospective analysis was conducted using the data from the Surveillance, Epidemiology, and End Results (SEER) program. Propensity score matching (PSM) was conducted to balance potential baseline confounding factors. Survival analyses were conducted using Kaplan-Meier and Cox regression methods. The present study included 33,393 inoperable patients with stage III NSCLC, including 106 patients treated with TA and 33,287 patients treated with radiotherapy. No statistical difference in overall survival (OS) (p = .065) or cancer-specific survival (CSS) (p = .996) was found between the patients treated with TA and those treated with radiotherapy. Using 1:3 matching, a matched cohort of 420 patients (105 patients treated with TA, 315 patients treated with radiotherapy) was identified. The differences in OS (p = .177) and CSS (p = .605) were still not significant between the radiotherapy and TA groups after PSM. According to subgroup analyses, TA showed comparable survival benefits in almost all subgroups compared to radiotherapy. For inoperable stage III NSCLC, the survival benefit of TA was comparable to radiotherapy. TA may be a potential therapeutic modality for inoperable stage III NSCLC.